2015
DOI: 10.1186/s12891-015-0457-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and copy number of SMN1, SMN2 and NAIP in Chinese patients with spinal muscular atrophy and unrelated healthy controls

Abstract: BackgroundSpinal muscular atrophy (SMA) is caused by SMN1 dysfunction, and the copy number of SMN2 and NAIP can modify the phenotype of SMA. The aim of this study was to analyze the copy numbers and gene structures of SMA-related genes in Chinese SMA patients and unrelated healthy controls.MethodsForty-two Chinese SMA patients and two hundred and twelve unrelated healthy Chinese individuals were enrolled in our study. The copy numbers and gene structures of SMA-related genes were measured by MLPA assay.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
1
20
3
1
Order By: Relevance
“…Another limitation of this model is that it is only generalizable to the subgroup of SMA1 patients with two copies of the SMN2 gene, due to the restricted nature of the clinical trials. However, these patients make up~80% of all patients with SMA1 [42,43]. SMA1 patients with three copies of SMN2 may have less severe disease although they still experience significant morbidity and mortality, and patients with only one copy of SMN2 are likely to have experienced irreversible motor neuron death before birth [42].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this model is that it is only generalizable to the subgroup of SMA1 patients with two copies of the SMN2 gene, due to the restricted nature of the clinical trials. However, these patients make up~80% of all patients with SMA1 [42,43]. SMA1 patients with three copies of SMN2 may have less severe disease although they still experience significant morbidity and mortality, and patients with only one copy of SMN2 are likely to have experienced irreversible motor neuron death before birth [42].…”
Section: Discussionmentioning
confidence: 99%
“…A study of Korean SMA patients that analyzed deletions in candidate genes (i.e., SMN1 , NAIP , and p44 ) did not find a genotype-phenotype correlation, but this could have due to the inclusion of only a small number of patients 20. In a study of Chinese patients, Fang et al21 compared copy numbers of SMN1 , SMN2 , and NAIP in SMA patients and healthy controls and produced evidence of differences in copy numbers and gene structure between the SMA patients and controls. Qu et al22 further investigated the association of copy numbers of SMN2 and NAIP with the disease course in SMA patients, and found that patients with fewer copies of SMN2 and NAIP were characterized by a higher risk of death and a lower survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Human SMN2 is localized to the unstable chromosomal region prone to duplication, deletion and gene conversion. Therefore, the number of SMN2 copies in humans varies [70]. In SMA-stricken patients with the large number of SMN2 copies the symptoms are mild [71].…”
Section: Lncrna Smn-as In the Development Of Spinal Muscular Atrophymentioning
confidence: 99%